Design of Robust, Lithiophilic, and Flexible Inorganic‐Polymer Protective Layer by Separator Engineering Enables Dendrite‐Free Lithium Metal Batteries with LiNi0.8Mn0.1Co0.1O2 Cathode. Issue 13 (10th March 2021) - Tan, Liwen; Sun, Yue; Wei, Chuanliang; Tao, Yuan; Tian, Yuan; An, Yongling; Zhang, Yuchan; Xiong, Shenglin; Feng, Jinkui
Abstract: As a promising candidate for the high energy density cells, the practical application of lithium‐metal batteries (LMBs) is still extremely hindered by the uncontrolled growth of lithium (Li) dendrites. Herein, a facile strategy is developed that enables dendrite‐free Li deposition by coating highly‐lithiophilic amorphous SiO microparticles combined with high‐binding polyacrylate acid (SiO@PAA) on polyethylene separators. A lithiated SiO and PAA (lithiated‐SiO/PAA) protective layer with synergistic flexible and robust features is formed on the Li metal anode via the in situ reaction to offer outstanding interfacial stability during long‐term cycles. By suppressing the formation of dead Li and random Li deposition, reducing the side reaction, and buffering the volume changes during the lithium deposition and dissolution, such a protective layer realizes a dendrite‐free morphology of Li metal anode. Furthermore, sufficient ionic conductivity, uniform lithium‐ion flux, and interface adaptability is guaranteed by the lithiated‐SiO and Li polyacrylate acid. As a result, Li metal anodes display significantly enhanced cycling stability and coulombic efficiency in Li||Li and Cu||Li cells. When the composite separator is applied in a full cell with a carbonate‐based electrolyte and LiNi0.8 Mn0.1 Co0.1 O2 cathode, it exhibits three times longer lifespan than control cell at current density of 5 C. Abstract : Highly‐lithiophilic amorphous SiO microparticles combined with high‐binding polyacrylate acid are used for polyethylene separators modification. As a result, an in situ artificial inorganic‐polymer protective layer with integrated merits of robustness and flexibility is formed on the Li metal anode to offer outstanding interfacial stability during long‐term cycles and enable dendrite‐free Li plating.